Development of halal literacy indicators based on reading literacy viewed from the dimensions of content, process, context, and attitude - Nurunnajib, Ahfazh Fauzy; Anwar, Dede Miftahul; Nurdin, Muhamad Ali; Nuryantini, Ade Yeti; Cahyanto, Tri; Windayani, Neneng (Journal of Halal Science and Research, 2025)
Halal literacy is increasingly important as consumers seek to make informed and ethical decisions about halal products and services. This study aims to develop comprehensive indicators for halal literacy by integrating the principles of reading literacy. The research involved a thorough literature review and expert consultations to identify key concepts and indicators relevant to halal literacy. The developed indicators are organized into four dimensions: Content, Process, Context, and Attitude. The Content dimension includes foundational knowledge, reliable sources, and an understanding of halal labels and certifications. The Process dimension emphasizes critical reading skills, decision-making, and technology utilization. The Context dimension highlights the influence of social and cultural environments and the role of education. The Attitude dimension focuses on personal commitment and awareness of halal literacy. The indicators were validated through thematic analysis and expert feedback, ensuring their relevance and applicability. The findings reveal a structured framework consisting of specific indicators across the four dimensions of Content, Process, Context, and Attitude, which can be utilized to enhance halal literacy. These indicators serve as practical tools for developing educational programs that equip individuals with the necessary knowledge and skills to make informed decisions about halal products. Additionally, the framework can guide community initiatives aimed at raising awareness and promoting halal practices, as well as inform policy-making to support halal literacy at a broader level. By integrating cognitive and affective dimensions, this study contributes to the broader discourse on literacy, emphasizing the importance of a comprehensive approach to understanding and practicing halal literacy. Keywords: Education, Indicators, Halal literacy, Reading literacy.